Supply chain adaptations for bundled service offers in the automotive aftermarket supply chain - Gudmundsdottir, Margret; Gustafsson, Emmelie (My University, 2015)
Aftermarket services are considered very important and are no longer an afterthought within companies. In fact, the aftermarket has turned into the main source of profit for companies. For OEMs to be able to upgrade and transform their aftermarket supply chains, they must understand what type of supply chain design that is appropriate given the performance requirements of the bundled service offers they provide. The current aftermarket supply chain at the case company was not originally designed around the bundled service offers, which puts pressure on the case company to adapt their aftermarket supply chain to be able to meet the challenges that the bundled service offers put on them. The purpose of this thesis is to study the bundled service offers in order to provide recommendations for adaptations of the aftermarket supply chain. In order to deliver the recommendations, an investigation of the key challenges with the aftermarket supply chain in regard to the bundled service offers currently offered by the case company will be conducted, as well as a benchmarking study on what other companies identify as supply chain challenges in regard to aftermarket services. The scope of this thesis only includes bundled service offers for Volvo Group Trucks in the Nordic market and the focus is on the offers that impact the aftermarket supply chain, the service contracts. There are three different types of service contracts provided by the case company; Blue, Silver and Gold. The content in the service contracts differs, which puts different demands on availability of spare parts. This thesis has contributed to the area of aftermarket supply chains when it comes to the understanding of how to achieve operational excellence through operationalization of service strategies. The conclusion is that from a physical handling perspective, the current aftermarket supply chain at the case company is considered sufficient, but some adaptations could be made to further improve it. Furthermore, the operational and organizational principles in terms of administrative handling of the current aftermarket supply chain can be improved. The recommendations consists of five areas of improvements. The first recommendation is prioritization of availability of critical spare parts according to service contract orders. This implies that the contract prioritization should be included in the current order classes, and the orders should be prioritized according to the service contracts. The second recommendation is prioritizing suppliers according to criticality, which means that suppliers supplying critical parts should be prioritized higher than the ones supplying less critical parts. The third recommendation is implementing local hubs close to the dealers, that serve more than one dealer in the area. This means that critical parts would be stored at the local hubs providing improved availability to meet the requirements of the service contracts. The fourth recommendation is to measure the total lead-time from order placed until delivered as a KPI to improve customer satisfaction. The last recommendation is improving internal information sharing between the functions sales and materials management when designing the service contracts, but also when supplying the spare parts.
Keywords: Transport; Övrig industriell teknik och ekonomi; Transport; Other industrial engineering and economics